Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. I. Dactyloidae, Hoplocercidae, Iguanidae, Leiosauridae, Polychrotidae, Tropiduridae - Ribeiro-Júnior, Marco A. (Zootaxa, 2015)
I present distribution data of all Dactyloidae, Hoplocercidae, Iguanidae, Leiosauridae, Polychrotidae and Tropiduridae lizards known from the Brazilian Amazonia, totaling 40 species-level taxa, belonging to 11 genera. This represents four more species-level taxa than previously reported for these families. Data were based on the direct examination of 41,243 specimens deposited in three North American and eight Brazilian musea, including the main collections harboring Amazonian material. Most species (62.5%) are endemic to the Amazonia; non-endemic species are mainly associated with open dry (semideciduous) forest or open vegetation (savanna) enclaves in Amazonia, with a few exceptions. As a whole, seven taxa are widespread in Amazonia, one is restricted to eastern Amazonia, three to western Amazonia, five to northern Amazonia (either in part of it or widespread in the Guiana region), two to northwestern Amazonia, one to southern Amazonia, nine to southwestern Amazonia, and seven to the southern peripheral portion of Amazonia. Five species have unique distributions and five species have a distribution that is congruent with one of the areas of endemism (AE) recognized for other organisms (birds and primates). The first herpetological gazetteer for the Brazilian Amazonia with about 3,600 georeferenced localities was also produced.